2006
DOI: 10.2337/diabetes.55.03.06.db05-0849
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hepatic Glycogen Breakdown in Defective Counterregulation of Hypoglycemia in Intensively Treated Type 1 Diabetes

Abstract: Impairment of hypoglycemic counterregulation in intensively treated type 1 diabetes has been attributed to deficits in counterregulatory hormone secretion. However, because the liver plays a critical part in recovery of plasma glucose, abnormalities in hepatic glycogen metabolism per se could also play an important role. We quantified the contribution of net hepatic glycogenolysis during insulininduced hypoglycemia in 10 nondiabetic subjects and 7 type 1 diabetic subjects (HbA 1c 6.5 ؎ 0.2%) using 13 C nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
5
40
1
1
Order By: Relevance
“…It is plausible that a preserved exercise-induced increase in circulating catecholamines rather than the glucagon response enabled continuous substrate mobilisation from the liver in this patient cohort [14,30,[36][37][38]. It is known that pre-exercise hypoglycaemia is associated with blunted counter-regulation and impaired hepatic glycogenolysis [23,39]. Since in the present study, patients were admitted overnight and hypoglycaemia was avoided prior to the experiment, counter-regulatory mechanisms were likely to have been preserved.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It is plausible that a preserved exercise-induced increase in circulating catecholamines rather than the glucagon response enabled continuous substrate mobilisation from the liver in this patient cohort [14,30,[36][37][38]. It is known that pre-exercise hypoglycaemia is associated with blunted counter-regulation and impaired hepatic glycogenolysis [23,39]. Since in the present study, patients were admitted overnight and hypoglycaemia was avoided prior to the experiment, counter-regulatory mechanisms were likely to have been preserved.…”
Section: Discussionmentioning
confidence: 77%
“…Human studies using magnetic resonance spectroscopy (MRS) have reported defects in mobilisation of hepatic glycogen stores in patients with type 1 diabetes [23,24]. However, these studies were performed either under very low circulating insulin concentrations (30-60 pmol/l) or after hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A multislice gradient echo imaging sequence was used for scout images (flip ϭ 45°, TR ϭ 0.8 s, TE ϭ 10 ms, FOV ϭ 32 or 48 mm 2 , slice thickness ϭ 2 mm). 31 P MRSI data were acquired using a 90°nonselective adiabatic hypersecant excitation pulse. Spectroscopic images were generated with a three-dimensional phase-encoding scheme using spherical sampling on a 13 ϫ 13 ϫ 13 grid (FOV ϭ 32 or 48 mm 2 , TR ϭ 0.4-0.6 s, 2 transients) with a total acquisition time of 30-40 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…2A displays a scout image and indicates regions of interest for the three 31 P magnetic resonance spectra shown in a study of the CK-Tg mice. PCr resonance was seen in each liver region of interest, indi- 31 P MRS spectra of CK-Tg mouse liver. CK-Tg mice were fed a liquid diet fortified with 10% creatine monohydrate for 4 days.…”
Section: Detection Of Ck Expression In Ck-tg Mouse Livermentioning
confidence: 99%
“…In intensively treated type 1 diabetes patients, hypoglycemia failed to stimulate hepatic glycogen breakdown or activation of endogenous glucose production, despite activation of counterregulation. According to the authors, these factors may contribute to the defective hypoglycemic counterregulation seen in type 1 diabetes patients [102].…”
Section: Glycogen Synthesis and Breakdown In Type 1 Diabetesmentioning
confidence: 99%